Stigma and its correlates among caregivers of schizophrenia: A study from North India. (30th July 2016) - Singh, Aakanksha; Mattoo, Surendra K.; Grover, Sandeep
Abstract: This study aimed to study stigma experienced by caregivers of patients with schizophrenia. One hundred caregivers of patients with schizophrenia were evaluated on Stigma scale for caregivers of people with mental illness (CPMI), Explanatory model interview catalogue stigma scale (EMIC), General health questionnaire-12 (GHQ), Self-report attitude towards medications questionnaire and Knowledge of mental illness scale (KMI). On CPMI the score was higher for affective component (2.3±0.5) than for cognitive (1.9±0.9) and behavioural (1.8±0.6) components. More than half of caregivers 'agreeing' or 'strongly agreeing' on 20 out of 22 items of CPMI indicated high level of stigma. On EMIC the stigma score was 21.7±6.3. Higher level of affiliate and/or associative stigma was associated with shorter duration of illness and treatment, shorter duration of being in the caregiver role, younger, female and non-earning caregivers, prescription of higher number of pills, caregivers who less often accompany the patient to the hospital and caregivers experienced more psychological morbidity. To conclude this study suggests that caregivers of patients with schizophrenia experience substantial stigma; hospital and community level programs and services are required to reduce and prevent the same. Highlights: Caregivers of patients with schizophrenia experience high level of stigma. Caregivers experienced more stigma in the affective domain than that experienced in the cognitive and behavioural domains. Higher stigma was predicted by caregiver's age, gender and psychological morbidity.